Biofilm colonization of stone materials from an Australian outdoor sculpture: Importance of geometry and exposure. (1st August 2023) - Cattò, Cristina; Mu, Andre; Moreau, John W.; Wang, Nancy; Cappitelli, Francesca; Strugnell, Richard
Abstract: The safeguarding of Australian outdoor stone heritage is currently limited by a lack of information concerning mechanisms responsible for the degradation of the built heritage. In this study, the bacterial community colonizing the stone surface of an outdoor sculpture located at the Church of St. John the Evangelist in Melbourne was analysed, providing an overview of the patterns of microbial composition associated with stone in an anthropogenic context. Illumina MiSeq 16S rRNA gene sequencing together with confocal laser microscope investigations highlighted the bacterial community was composed of both phototrophic and chemotrophic microorganisms characteristic of stone and soil, and typical of arid, salty and urban environments. Cardinal exposure, position and surface geometry were the most important factors in determining the structure of the microbial community. The North-West exposed areas on the top of the sculpture with high light exposure gave back the highest number of sequences and were dominated by Cyanobacteria. The South and West facing in middle and lower parts of the sculpture received significantly lower levels of radiation and were dominated by Actinobacteria. Proteobacteria were observed as widespread on the sculpture. This pioneer research provided an in-depth investigation of the microbial community structure on a deteriorated artistic stone in the Australian continent and provides information for the identification of deterioration-associated microorganisms and/or bacteria beneficial for stone preservation. Highlights: A pioneer study of biofilm on stone heritage in Australia. Structure, diversity and interactions of biofilms on the outdoor stones was studied. Community was composed of both phototrophic and chemotrophic bacteria. Proteobacteria, Actinobacteria and Cyanobacteria were dominant phyla. Bacterial community was shaped by cardinal exposure, position and surface geometry.